Demystifying Evaluation : Practical Approaches for Researchers and Users - Parsons, David (Book collections on Project MUSE., 2017)
Social research practitioners and others working in the public and voluntary sectors, in academia and consultancy are increasingly under pressure to provide policy-related evidence with limited resources and rising expectations. Demystifying evaluation is an accessible introductory guide setting the foundations for tackling those challenges, explaining the options open to evaluators, their merits and uses, and how to make appropriate choices of research methods. Drawing on his experience of policy and programme evaluations for the public sector and outside, David Parsons provides a practica.